PERANCANGAN MEDIA PROMOSI SUOKLAT DENGAN TEKNIK VEKTOR SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Rosyanto, Ikmal Imani; Budiardjo, Hardman; Martono, Siswo (Jurnal Art Nouveau, 2016)
Abstract:Suoklat is a company with a product that is first processed chocolate in Surabaya. Suoklat have a variety of processed chocolate products and has a unique packaging each product. When Suoklat studied, Suoklat only two promotion media to support the promotion of the company. Suoklat has a good potential of the market in Surabaya, therefore, the researchers wanted to reintroduce Suoklat to the public. Researcher using a design approach Suoklat promotion media to introduce to the public because promotion media which is considered to be a mass media that the effect can be immediate. media campaign that used the other researchers, billboards, flyers, mobile billboards, merchandise, website. Selection of the media campaign refers to the STP analysis as it relates to the market. Researchers expect from an alternative solution that is designed by the researchers can create Suoklat be a company known by the public.Keywords: Design, Promotion, Communication Visual, Brand Awareness